Designing a Qualitative Model of the Micro Foundations of Dynamic Capabilities in Cloud Computing Service Providers in Iran - Afshin Ghasemi; MohammadTaghi Isaai; Reza Bandarian; Ahmad EkhtiarZadeh (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The present study seeks to provide a qualitative model of the micro-foundations of dynamic capabilities in cloud computing companies in Iran. For this purpose, the micro-foundations of the three areas of Sensing, seizing, and reconfiguring have been extracted based on the reference model of Teece (2007).Methodology: The research methodology is an extended case study. Due to the novelty of the research topic and the lack of a reference model, research components were collected through a review of optimal experiences and in-depth interviews with key managers of organizations. For this reason, we created a theoretical saturation by compiling a protocol of interviews and conversations with 14 senior managers of active companies in Iran's cloud computing field. Then, through qualitative content analysis, the components were extracted.Findings: In the micro-foundations of the field of Sensing, the three constructs of senior managers' intuition, the trend of consumer behaviour in countries similar to the consumer behaviour of Iran's ICT field, and the study of export opportunities differ from the results of previous research. The three construct technology knowledge transfer, best practice, and legal requirements of ISO and quality are among the categories less mentioned in earlier research. Finally, contingent strategic management, organizational strategic empathy, customer experience management, and strategic perseverance have been less studied in reconfiguring. In general, the critical role of senior managers in leading issues and creating empathy and appropriate cooperation with staff and customers as the main profile of managers has been considered to promote dynamic empowerment in organizations.Originality/Value: Due to the nature of technology and economic, political, and social governance of Iranian IT companies, it is necessary to provide a clear roadmap for this sector by identifying the micro-foundations of dynamic capabilities